Exsudado do cultivo da levedura Rhodotorula glutinis no potencial fisiológico e armazenamento de sementes de soja - Carraro, Bianca Pierina (2022)
For a more sustainable agriculture, research on biological products based on yeast has been presented as a promising alternative for the preservation of natural resources, since such microorganism has the ability to produce phytohormones, promoting the growth and development of plants, in addition to post-harvest conservation. Therefore, the selection of high-quality seeds allows access to genetic and technological advances adapted to different regions, ensuring greater productivity. Thus, this study evaluated the effects of the exudate from Rhodotorula glutinis yeast on the physiological potential of soybean seeds and their storability. The isolate was inoculated in YEPG-broth in order to produce the exudate. After 14 days, the material was centrifuged and the supernatant part was collected. This was followed by lyophilization and storage of the exudate. For the detection and quantification of phytohormones, samples of the lyophilized exudate and liquid were sent for analysis by liquid chromatography coupled to mass spectrometry (LC/MS/MS). The effect of the yeast exudate was initially evaluated in the treatment of lettuce seeds (indicator plant) at concentrations of 12.5 mg mL-1 , 25.0 mg mL-1 , 37.5 mg mL-1 , 50.0 mg mL-1 and a control in a completely randomized design with 4 replications. Germination and vigor tests were carried out and variables such germination percentage, germination speed index, average shoot length, average root length and dry mass were analyzed. From the results on lettuce, the effect of the yeast exudate in the soybean seeds treatment was verified at concentrations of 25.0; 50.0; 75.0; 100.0; 125.0 and 150.0 mg mL-1 , with the control consisting of distilled water. Germination and vigor tests were performed observing the germination percentage, hypocotyl and root length, vigor index and seedling growth index. The experimental design was completely randomized with seven treatments and five replications. With the aim of evaluating the physiological potential of soybean treated with the yeast exudate and stored, the experiment was conducted in a 3x5 bifactorial randomized block design (RBD), with factor 1 being storage (0, 60 and 180 days) and factor 2 being different concentrations of the yeast exudate (control, 25, 50, 75 and 100%), with 4 replications per treatment. The parameters evaluated were germination percentage, average root length, average shoot length, dry mass, electrical conductivity, emergence speed index and emergence speed. In the lyophilized exudate of the Rhodotorula glutinis (AH 14-3) yeast, there was a synthesis of gibberellin type GA4 and, in the liquid exudate, the auxins indole-3-acetic acid (IAA) and indole-3-butyric acid (IBA) were detected, which promoted the germination and growth of lettuce and soybean seedlings. On lettuce, the effect of the yeast exudate was significant at 50.0 mg mL-1 , increasing shoot length by 58% and root length by 74%. On soybean, the yeast exudate concentration of 25.0 mg mL 1 stimulated an increase of 55% in hypocotyl size, 164% in radicle size, 91% in vigor index and 156% in growth index. During the storage period of soybean seeds treated with the yeast exudate, the variables of germination percentage, emergence speed index and emergence speed showed a significant reduction when 180 days were reached, demonstrating a deterioration process. As for the variables of root length, shoot length and dry mass, an increase of 88, 40 and 51% was observed, respectively, at 180 days of storage, suggesting an increase in seed vigor. Electrical conductivity decreased by 35% over time, also indicating an increase in vigor. In the interaction between storage factors and yeast exudate concentrations for the emergence speed index, concentrations of 50 and 75% maintained the results at 180 days of storage, being statistically equal to the results obtained at 60 days, which indicates the maintenance of seed quality. Given all the good results that were found, it is believed that the exudate of the Rhodotorula glutinis yeast has an action that promotes ix germination and plant growth due to the phytohormones present. In the six months of storage, the soybean seeds showed deterioration at 60 days. However, at 180 days the quality was maintained. Other studies may elucidate the mechanisms of action of phytohormones and detect the presence of other molecules that promote plant growth.